Об одном подходе к персонификации диагностических решений на примере оценки сердечной деятельности - Файнзильберг, Л.С. (Кибернетика и вычислительная техника, 2014)
Предложен подход к персонифицированной диагностике, основанный на оценке индивидуальной нормы конкретного пользователя по результатам многократных наблюдений. Рассмотрены схемы персонифицированных решений, предусматривающие анализ взаимного расположения в пространстве диагностических признаков областей индивидуальной и популяционной норм. Приведены примеры персонифицированных диагностических решений для оценки текущего состояния сердечно-сосудистой системы. Запропоновано підхід до персоніфікованої діагностики, заснований на оцінці індивідуальної норми конкретного користувача за результатами багаторазових спостережень. Розглянуто схеми персоніфікованих рішень, що передбачають аналіз взаємного розташування в просторі діагностичних ознак областей індивідуальної та популяційної норм. Наведені приклади персоніфікованих діагностичних рішень для оцінки поточного стану серцево-судинної системи. The purpose of the article is to propose a common scheme to build personalized diagnostic solutions and demonstrate the possibility of the practical using of this scheme in the evaluation of the current functional state of the cardiovascular system taking into account the individual characteristics of a particular patient electrocardiogram. Results: It is shown that the proposed approach can be simply implemented on modern means of digital medicine. This is demonstrated using the example of a diagnostic facility FASEGRAPH®, which provides automatic calculation of the original diagnostic feature Tb — the symmetry of the repolarization fragment of the ECG’s averaged phase trajectory. The device has the scheme of personalized solutions based on automatic identification of personalized standards and personalized standard deviation of the feature Tb .